2005
DOI: 10.1682/jrrd.2005.06.0094
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-induced movement therapy for recovery of upper-limb function following traumatic brain injury

Abstract: Abstract-A volunteer sample of 22 participants with chronic traumatic brain injury (TBI) (onset >1 year) and relative hemiplegia that revealed moderate disability in the more-affected upper limb (UL) participated. Constraint-induced (CI) movement therapy (CI therapy) was employed for a 2-week period; treatments included massed practice, shaping of the moreaffected UL, behavioral contracts, and other behavioral techniques for affecting transfer to a real-world setting. We used the Wolf Motor Function Test, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 40 publications
(56 reference statements)
3
72
0
1
Order By: Relevance
“…Patients with TBI have been shown to have positive rehabilitation outcomes as a result of high numbers of functional reps, such as is required in constraint-induced movement therapy (CIMT) [20]. Patients with TBI who received additional functional reps (+160 reps of sit-tostand and step-ups) had a larger functional improvement compared with a group who did not receive the additional reps, suggesting that the dose of rehabilitation is also important in TBI [21].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with TBI have been shown to have positive rehabilitation outcomes as a result of high numbers of functional reps, such as is required in constraint-induced movement therapy (CIMT) [20]. Patients with TBI who received additional functional reps (+160 reps of sit-tostand and step-ups) had a larger functional improvement compared with a group who did not receive the additional reps, suggesting that the dose of rehabilitation is also important in TBI [21].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the CIMT achieved voluntary purposeful behavior consistent with presurgical limb function, providing further support for Taub's hypothesis of learned nonuse. While early human clinical research focused on the use of CIMT following stroke [20,25], a series of internationally funded scientific studies subsequently demonstrated applicability following other traumas, including upper limbs after TBI, lower limbs after stroke, spinal cord injury, fractured hip, and aphasia after stroke [32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…These include the differential control of electroencephalography to reduce medically unresponsive epileptic seizures [57][58] and other conditions [59], as well as the aforementioned training and recovery of affected limbs following stroke [3], the upper limbs after TBI, the lower limbs after stroke, spinal cord injury, fractured hip, and aphasia after stroke [33][34][35][36][37]. What has also been demonstrated is that the presence of verbal report or lack of memory does not determine whether voluntary control of physiological response can be trained.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supports the general effectiveness of physical rehabilitation in improving TBI outcomes (Bland, Zampieri-Gallagher, and Damiano, 2011;Betker, Desai, Nett, Kapadia, and Szturm, 2007;Irdesel, Aydiner, and Akgoz, 2007;Mossberg, Amonette, and Masel, 2010;Scherer and Schubert, 2009;Shaw et al, 2005). Persons who have little or no response to stimulation (i.e., comatose, vegetative or minimally conscious state) benefit from activities that prevent involuntary muscle contraction or muscle shortening and skin breakdown.…”
Section: Effectiveness Of Physical Rehabilitationmentioning
confidence: 94%